2021
DOI: 10.1149/2162-8777/ac19c4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Phase Stability of Formamidinium Lead Triiodide by Addition of Calcium Chloride

Abstract: Formamidinium lead triiodide (FAPbI 3 ) with stable black perovskite phase and without significantly changing its bandgap is demonstrated by the incorporation of CaCl 2 . More incorporated CaCl 2 in FAPbI 3 creates a desirable crystal structure, satisfying the Goldschmidt tolerance factor, and thereby stabilizing black perovskite phase under ambient conditions. However, more incorporated CaCl 2 in FAPbI 3 is likely to degrade the perovskite due to its hygroscopic characteristics. In addition, the incorporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[84] As mentioned earlier, small cations are often used to replace Pb 2+ at the B-site to reduce the lattice constant, optimize the tolerance factor, and improve the performance of the device. [16,77,92] Higher doping concentrations are better for the tolerance factor. However, this is not the case.…”
Section: Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[84] As mentioned earlier, small cations are often used to replace Pb 2+ at the B-site to reduce the lattice constant, optimize the tolerance factor, and improve the performance of the device. [16,77,92] Higher doping concentrations are better for the tolerance factor. However, this is not the case.…”
Section: Solar Cellsmentioning
confidence: 99%
“…After aging at 20 °C and 20% relative humidity for 500 h, the efficiency of the optimized sample decreased by 26.72% while that of the undoped sample decreased by 97.42%. [ 92 ] Additionally, Yao and co‐workers indicated that the average grain size of CsPbI 3 perovskite film with or without Mn addition was ≈350 nm (0%), ≈563 nm (2%), and ≈479 nm (4%). The lifetime of the champion carrier was 5.84 ns for the CsPbI 3 film doped with 2%, about twice that of 0% (2.99 ns).…”
Section: Applicationsmentioning
confidence: 99%